BRIEF OF BUILDING INFORMATION MODELLING FOR INDONESIAN ARCHITECTURE - Harsritanto, Bangun IR; Putra, Gentina Pratama; Jamila, Rona Fika (MODUL, 2019)
Building information modelling (BIM) is a system that integrates multi-dimensional aspects of construction project at every phase. Simply said BIM unified all project databases from and to all stakeholders. This system still continuously developed and widely spread on each countries construction projects. In architecture, the BIM has been revolute the human resource requirements on the projects. Indonesia as developing country is still performing transitions from large worker project into more compact projects; from centralized projects into decentralized project. The BIM system has been a mandatory in several Indonesia big infrastructure projects to plan, simulate, design and deliver databases for making more quick decision making and improve the facilities. This paper aim is describing the benefit-challenge factors of BIM adoption on Indonesia architecture projects and the potential driving factors of BIM application. This study was qualitative paradigm with analysis method of selected literatures and previous research paper review which stratified by the cases. The results of this study are BIM bring the high efficiency and represent the complete skills for an architect. However the high initial cost of technology and human investment, the unsupported regulation and conventional system resistant challenged the Indonesia architecture society to adopt BIM. Furthermore the Indonesia architecture education is still struggling to learn and teach the BIM as an integral part in studio as the agent of change.